High extracellular matrix metalloproteinase inducer/CD147 expression is strongly and independently associated with poor prognosis in colorectal cancer - Stenzinger, Albrecht; Goeppert, Benjamin; Weichert, Wilko (Human pathology, 2012)
Summary. As in most solid tumors, colorectal cancer prognosis strongly depends on the extent of local invasion and lymph node and distant metastases. Extracellular matrix metalloproteinase inducer (EMMPRIN) is a transmembrane glycoprotein that activates matrix metalloproteinases, a group of enzymes that play an important role in tumor invasion and metastasis formation. This study investigates the EMMPRIN expression in a large cohort of patients with colorectal cancer. Immunohistochemical analysis of tissue microarrays from 285 patients shows that increased EMMPRIN protein expression does not correlate with clinicopathologic parameters and is an independent prognostic factor of poor survival, with mean survival times of 103 months in EMMPRIN negative/low versus 57 months in EMMPRIN intermediate/high patients (P < .001). This pronounced association of increased EMMPRIN levels and—on average—a 45% reduction in overall survival could help improve the risk stratification in patients with colorectal cancer; moreover, the lack of correlations with classical measures of cancer invasion/spreading may suggest the relevance of alternative EMMPRIN pathways beyond matrix metalloproteinase activation.
Gesehen am 02.09.2020